Sistem Akuaponik “Kulkas Hidup” Untuk Daerah Lahan Terbatas, Sulit Air dan Daerah Pasca Bencana - Tulas Aprilia (Jurnal Perikanan Terapan, 2021)
The high population growth has led to less land for agriculture and fisheries, while the demand for food is increasing. The purpose of this study was to determine the survival rate of fish, daily growth rate, feed convertion ratio, character of aquaponic media, vegetable productivity, and water quality in a aquaponics.The results obtained by the survival rate at a fish density of 5 kg/bucket were 77-81%. The daily weight growth rate and feed convertion ratio at a fish density of 5 kg/bucket with feeding frequency of one time more effective. The character of the live system aquaponics media has many advantages, namely: water saving, simple system, no need for electricity, suitable for areas with minimal land, low investment costs, easy to implement, suitable for household production, the density of fish being raised is quite high. The productivity of vegetables is also good, the plant density is quite high, and good water quality. The aquaponics system of “kulkas hidup” can be used as a solution for food availability in densely populated areas, limited water areas and post-disaster areas. Keywords: Aquaponics, Kulkas Hidup, Food, Post Disaster